Ulcerative Colitis-Derived Colonoid Culture: A Multi-Mineral-Approach to Improve Barrier Protein Expression - Aslam, Muhammad N.; McClintock, Shannon D.; Attili, Durga; Pandya, Shailja; Rehman, Humza; Nadeem, Daniyal M.; Jawad-Makki, Mohamed Ali H.; Rizvi, Areeba H.; Berner, Maliha M.; Dame, Michael K.; Turgeon, Danielle Kim; Varani, James (Frontiers in Cell and Developmental Biology, 2020)
Recent studies demonstrated that Aquamin®, a calcium-, magnesium-, and multiple trace element-rich natural product, improves barrier structure and function in colonoids obtained from the tissue of healthy subjects. The goal of the present study was to determine if the colonic barrier could be improved in tissue from subjects with ulcerative colitis (UC). Colonoid cultures were established with colon biopsies from 9 individuals with UC. The colonoids were then incubated for a 2-week period under control conditions (i.e., in culture medium with a final calcium concentration of 0.25 mM) or in the same medium supplemented with Aquamin® to provide 1.5 – 4.5 mM calcium. Effects on differentiation and barrier protein expression were determined using several approaches: phase-contrast & scanning electron microscopy, quantitative histology & immunohistology, mass spectrometry-based proteome assessment and transmission electron microscopy. Although there were no gross changes in colonoid appearance, there was increase in lumen diameter and wall thickness on histology and greater expression of cytokeratin 20 along with reduced expression of Ki67 by quantitative immunohistology observed with intervention. In parallel, upregulation of several differentiation-related proteins seen in a proteomic screen with the intervention. Aquamin®-treated colonoids demonstrated a modest up-regulation of tight junctional proteins but stronger induction of adherens junction and desmosomal proteins. Increased desmosomes were seen at the ultrastructural level. Proteomic analysis demonstrated increased expression of several basement membrane proteins and hemidesmosomal components. Proteins expressed at the apical surface (mucins and trefoils) were also increased as were several additional proteins with anti-microbial activity or that modulate inflammation. Finally, several transporter proteins that affect electrolyte balance (and, thereby affect water resorption) were increased. At the same time, growth and cell cycle regulatory proteins (e.g., Ki67, nucleophosmin, and stathmin) were significantly down-regulated. Laminin interactions, matrix formation and extracellular matrix organization were the top up-regulated pathways with the intervention. A majority of individuals including patients with UC do not reach the recommended daily intake for calcium and other minerals. To the extent that such deficiencies might contribute to the weakening of the colonic barrier, the findings employing UC tissue-derived colonoids here suggest that adequate mineral intake might improve the colonic barrier.